Preparation method of lithium metal negative electrode with ultrathin lithium-loving high-entropy alloy interface layer

CN119447197APending Publication Date: 2025-02-14NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411654543.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Negative electrode-free lithium metal batteries show poor circulation stability during the cycle, mainly due to the irreversible loss of lithium resources and the generation of lithium dendrites.

Method used

Using the lithium metal negative electrode preparation method with an ultra-thin lithium-philic high-entropy alloy interface layer, high-entropy alloy powder, and hydrophobic polymer are dispersed in a non-organic solvent and applied to copper foil to form high-entropy The pre-physical and chemical interface layer of the alloy. This interface layer induces carbon nanotubes to form a 3D conductive network framework through catalytic elements, inhibiting the production of lithium dendrites and 'dead lithium'.

Benefits of technology

It effectively improves the stability of the lithium metal negative electrode during the charge and discharge cycle, slows down the volume change of the lithium metal negative electrode, and improves the cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447197A_ABST
    Figure CN119447197A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium metal negative electrode with an ultrathin lithium-loving high-entropy alloy interface layer, and belongs to the technical field of lithium metal batteries. The preparation method comprises the following steps: dispersing a carbon nanotube coated high-entropy alloy composite material, lithium tin alloy powder and a hydrophobic polymer in a non-organic solvent, coating a copper foil with the mixture, and drying the copper foil to obtain an ultrathin, pre-lithiated and lithium-loving negative electrode of a high-entropy alloy interface layer. According to the preparation method of the lithium metal negative electrode with the ultrathin lithium-loving high-entropy alloy interface layer, catalytic elements in the high-entropy alloy composite material coated with the carbon nanotubes are used for inducing the carbon nanotubes to form a 3D conductive network framework, so that the current density of the electrode can be effectively reduced, lithium metal deposition can be accommodated, and the lithium metal negative electrode has a good application prospect. And meanwhile, release of lithium ions in the lithium tin alloy can be activated for lithium pre-supplement, so that generation of lithium dendrites and dead lithium is inhibited, the volume change of a lithium metal negative electrode in the charge-discharge cycle process is slowed down, and the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular relates to a method for preparing a lithium metal negative electrode with an ultra-thin lithium-philic high-entropy alloy interface layer. Background Art

[0002] As people's demand for high energy density rechargeable technology continues to grow, traditional lithium-ion batteries based on lithium-ion intercalation chemistry can no longer meet the requirements of lithium battery energy density in various emerging fields. Lithium metal anodes have high theoretical specific capacity (3860 mAh g -1 ), low redox potential (-3.04 V compared to standard hydrogen electrode) and low mass (0.534 g·cm -3 ), is considered one of the most promising candidates for negative electrode materials. However, excessive use of lithium metal negative electrodes will increase processing difficulties and bring safety risks, thus hindering the large-scale application of lithium metal batteries.

[0003] The anode-free lithium metal battery (AF-LMB) is a new type of battery technology. Its main feature is that the anode is formed by depositing lithium metal during the first charge, and no lithium metal is used in the production process. This design improves the energy density of the battery, reduces production costs, and simplifies the manufacturing process. However, due to the extremely limited lithium source of the anode and its continuous loss during the continuous deposition and stripping process, the anode-free battery usually exhibits poor cycle stability. In addition, without the protection of a stable host material on the anode side or the compensation of excess active lithium, the irreversible loss of lithium resources caused by the generation of "dead lithium" and the side reactions between the electrolyte and metallic lithium during the cycle will be directly reflected in the loss of battery capacity.

[0004] To date, considerable empirical strategies have been accumulated for strengthening the substrate interface stability and controlling electrochemical deposition, such as constructing artificial coatings such as oxides, nitrides, and sulfides with high mechanical stiffness and ion diffusivity to suppress the growth of dendrites during the nucleation stage. However, under long-term cycling or high capacity loading, loosely packed inorganic units tend to separate from the substrate, resulting in the formation of Li-ion-rich species at the interface. x M intermediate layer, alleviating the nucleation barrier of Li. At the same time, the formation of alloys inevitably involves the problems of volume expansion, particle agglomeration and even electrode crushing, and the polymer interfacial layer with nucleophilic functional groups will deplete the limited lithium ions in the positive electrode and the poor electrolyte. Contents of invention

[0005] The purpose of the present invention is to provide a method for preparing a lithium metal negative electrode with an ultra-thin lithium-philic high-entropy alloy interface layer, so that zinc and aluminum elements serve as lithium-philic elements and become active adsorption sites; at the same time, any one or more elements of nickel, copper, iron or cobalt are used as catalytic metal elements to catalyze the growth of carbon nanotubes, effectively inhibiting the generation of lithium dendrites, and lithium-tin alloy powder compensates for the irreversible consumption of lithium ions caused by alloying, thereby improving the cycle stability.

[0006] To achieve the above-mentioned object, the present invention provides a method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high-entropy alloy interface layer, comprising the following steps: 1. A method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high-entropy alloy interface layer, characterized in that it comprises the following steps: S1. Preparing a high-entropy alloy composite material coated with carbon nanotubes: dissolving zinc nitrate, aluminum nitrate and other nitrates in deionized water and stirring to obtain a nitrate solution, adding citric acid to the nitrate solution to prepare a high-entropy alloy precursor, and grinding the high-entropy alloy precursor to obtain a high-entropy alloy precursor powder; preparing a high-entropy alloy composite material coated with carbon nanotubes by recrystallization of the high-entropy alloy precursor powder in an atmosphere of an inert gas and acetylene mixed gas; S2. Preparation of lithium-tin alloy particles: In an inert atmosphere, nano-tin particles with a particle size less than 200 nm and lithium metal are mixed in a molar ratio of 1-10:4.4-50, and heated at a temperature of 200°C-450°C for 6h-24h to obtain a lithium-tin alloy phase Li x Sn, grinding and sieving the lithium-tin alloy phase to obtain lithium-tin alloy particles; S3. In an inert atmosphere, a high entropy alloy composite material coated with carbon nanotubes and a hydrophobic polymer are dispersed in a non-polar solvent in a ratio of 6-12:1 to form a mixed solution. Lithium-tin alloy particles are added to the mixed solution and stirred evenly. A scraper is used to directly apply a certain thickness of the mixed solution on a copper foil. The mixed solution is then vacuum dried at a temperature of 60°C-120°C for 12h-24h to obtain a lithium metal negative electrode having a pre-lithiation interface layer of a high entropy alloy.

[0007] Preferably, in step S1, the molar ratio of zinc nitrate to aluminum nitrate is 1:1, and the molar ratio of zinc nitrate to other nitrates is 1:1.

[0008] Preferably, the other nitrate in step S1 is one or more of nickel nitrate, iron nitrate and cobalt nitrate.

[0009] Preferably, in step S1, the molar ratio of citric acid to the total amount of nitrate solution is 1:1, and the preparation of the high entropy alloy precursor specifically includes the following steps: S1-1, citric acid is dissolved in nitrate solution and stirred evenly to obtain a sol S1-2, placing the sol in an oven and heating it at 60°C to 100°C for 12h to 48h to obtain a dry gel; S1-3. The dry gel is placed in an inert atmosphere at 250° C. to 350° C. and heated for 25 min to 60 min for self-combustion to obtain a high entropy alloy precursor.

[0010] Preferably, in step S1, the specific steps of preparing a carbon nanotube-coated high entropy alloy composite material from a high entropy alloy precursor powder are as follows: the high entropy alloy precursor powder is spread flat on a magnetic boat, placed in a tubular furnace, an inert gas is introduced, and heated to 600°C-800°C at a heating rate of 2°C / min-15°C / min, and then an inert gas and acetylene mixture is introduced for 0.5h to 1h, and the mixture is cooled with the furnace to obtain a carbon nanotube-coated high entropy alloy composite material.

[0011] Preferably, the hydrophobic polymer in step S3 is one or more of polyvinylidene fluoride-hexafluoropropylene, ethylene vinyl acetate copolymer, polyvinylidene fluoride, octadecyl phosphate, polypropylene and polyacrylonitrile.

[0012] Preferably, in step S3, the input mass ratio of lithium-tin alloy particles to the high-entropy alloy composite material wrapped by carbon nanotubes is 1-3:10.

[0013] Preferably, in step S3, the non-polar solvent is one or more of toluene, tetrahydrofuran, cyclohexane, methyl formate and 1,3-dioxolane.

[0014] Preferably, in step S3, the mixed solution is scraped onto the copper foil to a thickness of 2 μm-20 μm.

[0015] Therefore, the present invention adopts the above-mentioned method for preparing a lithium metal negative electrode with an ultra-thin lithium-philic high-entropy alloy interface layer, and its beneficial effects are: High entropy alloy, lithium tin alloy powder and hydrophobic polymer are dispersed in a non-organic solvent and coated on copper foil to obtain a lithium metal negative electrode with a high entropy alloy pre-physical and chemical interface layer. Among them, the catalytic elements in the high entropy alloy induce carbon nanotubes to form a 3D conductive network skeleton, which can not only effectively reduce the current density of the electrode, but also accommodate lithium metal deposition, and at the same time activate the release of lithium ions in the lithium tin alloy for pre-replenishment of lithium, thereby inhibiting the generation of lithium dendrites and "dead lithium", slowing down the volume change of the lithium metal negative electrode during the charge and discharge cycle, and improving the cycle stability of the battery.

[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0018] Figure 1 Scanning electron microscope (SEM) image of FeCoNiAlZn@CNT prepared in Example 1 of the present invention; Figure 2 This is a transmission electron microscope (TEM) image of FeCoNiAlZn@CNT prepared in Example 1 of the present invention; Figure 3 This is an X-ray diffraction spectrum (XRD) of FeCoNiAlZn@CNT prepared in Example 1 of the present invention; Figure 4 Li prepared for Example 1 of the present invention 22 Transmission electron microscope (TEM) diagram of Sn5; Figure 5 Li prepared for Example 1 of the present invention 22 X-ray diffraction spectrum (XRD) of Sn5; Figure 6 FeCoNiAlZn@CNT-Li prepared in Example 1 of the present invention 22 Scanning electron microscope energy spectrum analysis (SEM-EDS) image of Sn5@EVA electrode; Figure 7 FeCoNiAlZn@CNT-Li obtained in Example 1 of the present invention 22 Sn5@EVA electrode and FeCoNiAlZn@CNT electrode obtained in comparative example 1 showed good stability at 1 mA·cm -2 , 3 mAh·cm -2 voltage-capacity curve; Figure 8 The Cu2NiAlZn@CNT-Li obtained in Example 2 of the present invention 22 Sn5@PVDF-HFP electrode and Cu2NiAlZn@CNT electrode obtained in comparative example 2 showed good stability at 1 mA·cm -2 , 3 mAh·cm -2 voltage-capacity curve; Fig. 9 The FeCoNiAlZn@CNT-Li obtained in Example 3 of the present invention 22 Sn5@PP electrode and FeCoNiAlZn@CNT electrode obtained in comparative example 3 showed good stability at 1 mA·cm-2 , 3 mAh·cm -2 voltage-capacity curve; Fig.10 The FeCoNiAlZn@CNT-Li obtained in Example 4 of the present invention 22 Sn5@PAN electrode and FeCoNiAlZn@CNT electrode obtained in comparative example 4 showed good stability at 1 mA·cm -2 and 3 mAh·cm -2 voltage-capacity curve; Fig.11 FeCoNiAlZn@CNT-Li obtained in Example 1 of the present invention 22 Sn5@EVA electrode and FeCoNiAlZn@CNT electrode obtained in comparative example 1 showed good stability at 1 mA·cm -2 and 3 mAh·cm -2 Coulomb efficiency when different numbers are lowered; Fig.12 FeCoNiAlZn@CNT-Li obtained in Example 1 of the present invention 22 Capacity retention curves of Sn5@EVA electrode and FeCoNiAlZn@CNT electrode obtained in comparative example 1 at 0.5C rate for full batteries prepared with matching commercial NCM811 positive electrode materials. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0020] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0021] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0022] The present invention is further described below with reference to the accompanying drawings and specific embodiments.

[0023] Embodiment 1 A method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer comprises the following steps: S1. Preparation of high entropy alloy composites coated with carbon nanotubes: 2.97g zinc nitrate, 3.75g aluminum nitrate, 2.9g nickel nitrate, 4g iron nitrate, and 2.38g cobalt nitrate were dissolved in 500mL deionized water and stirred to obtain a nitrate solution, and 1.92g citric acid was dissolved in the nitrate solution and stirred evenly to obtain a sol. The sol was placed in an oven and heated at 60°C for 12h to obtain a dry gel. The dry gel was placed in an Ar gas atmosphere and heated at 300°C for 30min for self-combustion to obtain a high entropy alloy precursor.

[0024] The high entropy alloy precursor was ground into powder and spread flat on a magnetic boat, placed in a tubular furnace, and Ar gas was introduced. After heating to 700°C at a heating rate of 2°C / min, a mixture of Ar gas and acetylene (gas flow ratio of 9:1) was introduced for 0.5h. The mixture was cooled in the furnace to obtain a carbon nanotube-coated high entropy alloy composite material FeCoNiAlZn@CNT.

[0025] S2. Preparation of lithium-tin alloy particles: In an Ar atmosphere, 1 g of nano-tin particles (particle size < 200 nm) and 4.4 g of lithium metal were mixed and heated at 250° C. for 6 h to obtain a lithium-tin alloy phase (Li 22 Sn5), grinding and sieving the lithium-tin alloy particles to obtain lithium-tin alloy particles.

[0026] S3. In an argon atmosphere, 0.8 g of lithium-tin alloy particles and 0.5 g of ethylene-vinyl acetate copolymer (EVA) were dispersed in toluene to form a mixed solution, and 4 g of carbon nanotube-coated high-entropy alloy composite material was added to the mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a scraper to a thickness of 15 μm, and then vacuum dried at 80 °C for 12 h to obtain FeCoNiAlZn@CNT-Li 22 Sn5@EVA's negative pole.

[0027] In a glove box filled with high-purity argon gas and with water and oxygen concentrations less than 0.1 ppm, FeCoNiAlZn@CNT-Li 22 The diameter of the Sn5@EVA negative electrode was cut to 12 mm, and lithium metal foil was used as the counter electrode to assemble into 2016 button cell A.

[0028] Embodiment 2 A method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer comprises the following steps: S1. Preparation of high entropy alloy composites coated with carbon nanotubes: Dissolve 5.9g zinc nitrate, 7.5g aluminum nitrate, 5.8g nickel nitrate and 5g copper nitrate in 800mL deionized water and stir to obtain a nitrate solution, dissolve 3.84g citric acid in the nitrate solution and stir evenly to obtain a sol. Heat the sol in an oven at 100°C for 24h to obtain a dry gel. Heat the dry gel at 250°C for 25min in an Ar gas atmosphere for self-combustion to obtain a high entropy alloy precursor.

[0029] The high entropy alloy precursor was ground into powder and spread on a magnetic boat, placed in a tubular furnace, and Ar gas was introduced. After heating to 800°C at a heating rate of 5°C / min, a mixture of Ar gas and acetylene (gas flow ratio of 8:1) was introduced for 0.5h and cooled in the furnace to obtain a high entropy alloy composite material coated with carbon nanotubes.

[0030] S2. Preparation of lithium-tin alloy particles: In an Ar atmosphere, 5 g of nano-tin particles (particle size < 200 nm) and 5.5 g of lithium metal were mixed and heated at 250° C. for 24 h to obtain a lithium-tin alloy phase (Li 22 Sn5), grinding and sieving the lithium-tin alloy particles to obtain lithium-tin alloy particles.

[0031] S3. In an argon atmosphere, 0.1 g of lithium-tin alloy particles and 0.125 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) were dispersed in toluene to form a mixed solution, and 1 g of a carbon nanotube-coated high-entropy alloy composite material was added to the mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a thickness of 15 μm using a scraper, and then vacuum dried at 80 °C for 12 h to obtain Cu2NiAlZn@CNT-Li 22 Sn5@PVDF-HFP negative pole.

[0032] In a glove box filled with high-purity argon gas and with water and oxygen concentrations less than 0.1 ppm, a slicer was used to slice the Cu2NiAlZn@CNT-Li 22 The diameter of the Sn5@PVDF-HFP negative electrode was cut to 12 mm, and lithium metal foil was used as the counter electrode to assemble into 2016 button cell B.

[0033] Embodiment 3 A method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer comprises the following steps: S1. Preparation of high entropy alloy composites coated with carbon nanotubes: 2.0g zinc nitrate, 2.5g aluminum nitrate, 1.9g nickel nitrate and 2.7g iron nitrate were dissolved in 1000mL deionized water and stirred to obtain a nitrate solution, and 1.28g citric acid was dissolved in the nitrate solution and stirred evenly to obtain a sol. The sol was placed in an oven and heated at 90°C for 48h to obtain a dry gel. The dry gel was placed in an Ar gas atmosphere and heated at 350°C for 60min for self-combustion to obtain a high entropy alloy precursor.

[0034] The high entropy alloy precursor was ground into powder and spread on a magnetic boat, placed in a tubular furnace, and Ar gas was introduced. After heating to 650°C at a heating rate of 10°C / min, a mixture of Ar gas and acetylene (gas flow ratio of 8:1) was introduced for 1 hour. The mixture was cooled in the furnace to obtain a high entropy alloy composite material coated with carbon nanotubes.

[0035] S2. Preparation of lithium-tin alloy particles: In an Ar gas atmosphere, 1.25 g of nano-tin particles (particle size < 200 nm) and 1.375 g of lithium metal were mixed and heated at 450° C. for 6 h to obtain a lithium-tin alloy phase (Li 22 Sn5), grinding and sieving the lithium-tin alloy particles to obtain lithium-tin alloy particles.

[0036] S3. In an argon atmosphere, 0.1 g of lithium-tin alloy particles and 0.285 g of polypropylene (PP) were dispersed in toluene to form a mixed solution, and 2 g of carbon nanotube-coated high-entropy alloy composite material was added to the mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a thickness of 15 μm using a scraper, and then vacuum dried at 80 °C for 12 h to obtain FeCoNiAlZn@CNT-Li 22 Sn5@PP's negative pole.

[0037] In a glove box filled with high-purity argon gas and with water and oxygen concentrations less than 0.1 ppm, FeCoNiAlZn@CNT-Li 22 The diameter of the Sn5@PP negative electrode was cut to 12 mm, and lithium metal foil was used as the counter electrode to assemble into a 2016 button cell C.

[0038] Example 4 A method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer comprises the following steps: S1. Preparation of high entropy alloy composites coated with carbon nanotubes: 0.297g zinc nitrate, 0.375g aluminum nitrate, 0.29g nickel nitrate, 0.4g iron nitrate, and 0.238g cobalt nitrate were dissolved in 300mL deionized water and stirred to obtain a nitrate solution, and 0.192g citric acid was dissolved in the nitrate solution and stirred evenly to obtain a sol. The sol was placed in an oven and heated at 100°C for 36h to obtain a dry gel. The dry gel was placed in an Ar gas atmosphere and heated at 300°C for 60min for self-combustion to obtain a high entropy alloy precursor.

[0039] The high entropy alloy precursor was ground into powder and spread on a magnetic boat, placed in a tubular furnace, and Ar gas was introduced. After heating to 700°C at a heating rate of 15°C / min, a mixture of Ar gas and acetylene (gas flow ratio of 7:1) was introduced for 0.5h. The mixture was cooled in the furnace to obtain a high entropy alloy composite material coated with carbon nanotubes.

[0040] S2. Preparation of lithium-tin alloy particles: In an Ar atmosphere, 2.5 g of nano-tin particles (particle size < 200 nm) and 2.75 g of lithium metal were mixed and heated at 300° C. for 10 h to obtain a lithium-tin alloy phase (Li 22 Sn5), grinding and sieving the lithium-tin alloy particles to obtain lithium-tin alloy particles.

[0041] S3. In an argon atmosphere, 0.8 g of lithium-tin alloy particles and 0.5 g of polyacrylonitrile (PAN) were dispersed in toluene to form a mixed solution, and 4 g of carbon nanotube-coated high-entropy alloy composite material was added to the mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a scraper to a thickness of 20 μm, and then vacuum dried at 120 °C for 24 h to obtain FeCoNiAlZn@CNT-Li 22 Sn5@PAN's negative pole.

[0042] In a glove box filled with high-purity argon gas and with water and oxygen concentrations less than 0.1 ppm, FeCoNiAlZn@CNT-Li 22 The diameter of the Sn5@PAN negative electrode was cut to 12 mm, and lithium metal foil was used as the counter electrode to assemble into a 2016 button cell D.

[0043] Comparative Example 1 2.1 g of FeCoNiAlZn@CNT and 0.3 g of EVA prepared in Example 1 were dispersed in toluene to form a mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a thickness of 15 μm using a scraper, and then vacuum dried at 80° C. for 12 h to obtain a FeCoNiAlZn@CNT negative electrode.

[0044] The FeCoNiAlZn@CNT negative electrode was cut into 12 mm in diameter using a slicer and assembled into a 2016 button cell E using lithium metal foil as the counter electrode.

[0045] Comparative Example 2 1 g Cu2NiAlZn@CNT and 0.125 g PVDF-HFP prepared in Example 2 were dispersed in toluene to form a mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a thickness of 15 μm using a scraper, and then vacuum dried at 80°C for 12 h to obtain a Cu2NiAlZn@CNT negative electrode.

[0046] The Cu2NiAlZn@CNT negative electrode was cut into 12 mm diameter using a slicer and assembled into a 2016 5 F button cell using lithium metal foil as the counter electrode.

[0047] Comparative Example 3 2 g of FeCoNiAlZn@CNT and 0.285 g of PP prepared in Example 3 were dispersed in toluene to form a mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a thickness of 15 μm using a scraper, and then vacuum dried at 80° C. for 12 h to obtain a FeCoNiAlZn@CNT negative electrode.

[0048] The FeCoNiAlZn@CNT negative electrode was cut into 12 mm in diameter using a slicer and assembled into a 2016 button cell G using lithium metal foil as the counter electrode.

[0049] Comparative Example 4 4 g of FeCoNiAlZn@CNT and 0.5 g of PAN prepared in Example 4 were dispersed in toluene to form a mixed solution. After stirring, the mixed solution was directly coated on a copper foil with a thickness of 20 μm using a scraper, and then vacuum dried at 120° C. for 24 h to obtain a FeCoNiAlZn@CNT negative electrode.

[0050] The FeCoNiAlZn@CNT negative electrode was cut into 12 mm in diameter using a slicer and assembled into a 2016 button cell H using lithium metal foil as the counter electrode.

[0051] Experimental Testing (1) The carbon nanotube-coated high entropy alloy composite FeCoNiAlZn@CNT prepared in Example 1 was characterized by SEM. Figure 1 shown.

[0052] Figure 1 The FeCoNiAlZn particles in the alloy induce the formation of interlaced carbon nanotubes, and the alloy grain size is no more than 100nm and is uniform in size.

[0053] (2) The carbon nanotube-coated high entropy alloy composite FeCoNiAlZn@CNT prepared in Example 1 was characterized by TEM. Figure 2 shown.

[0054] from Figure 2 From the TEM images, it can be seen that the lattice spacing of the FeCoNiAlZn alloy is 0.21nm and 0.15nm; in addition, the lattice spacing of the adjacent graphitized carbon tubes is 0.33nm.

[0055] (3) XRD test was performed on the carbon nanotube-coated high entropy alloy composite FeCoNiAlZn@CNT prepared in Example 1. Figure 3 The XRD test results show that the FeCoNiAlZn synthesized in Example 1 is a pure phase.

[0056] (4) The Li prepared in Example 1 22 Sn5 particles were characterized by TEM. Figure 4 As shown, it can be seen that the particle size of the synthesized lithium-tin alloy phase is about 200 nm.

[0057] (5) The Li prepared in Example 1 22 Sn5 particles were tested by XRD, and the results were as follows Figure 5 As shown. It can be seen that the synthesized Li 22 Sn5 is completely matched with the standard card (PDF#18-753) and no impurity phase exists.

[0058] (6) The FeCoNiAlZn@CNT-Li prepared in Example 1 22 Sn5@EVA negative electrode was characterized by SEM, and the scanning electron microscope energy spectrum analysis (SEM-EDS) was shown in the figure Figure 6 As shown in the figure, the coating thickness of this embodiment is 13.5 μm, and from the EDS graph, it can be seen that the six elements Fe, Co, Ni, Al, Zn, and Sn are evenly distributed.

[0059] (7) After the prepared 2016 button batteries A to H were placed for 12 h, the electrochemical performance was tested using the Xinwei battery channel in constant current mode.

[0060] 1) AH was divided into four control groups: 2016 button battery A and 2016 button battery E as the first control group, 2016 button battery B and 2016 button battery F as the second control group, 2016 button battery C and 2016 button battery G as the third control group, 2016 button battery D and 2016 button battery H as the fourth control group. -2 Deposition / stripping at a constant current density of 3 mAh·cm-2 The voltage-capacity curves of metallic lithium are as follows: Figure 7-10 As shown, the first-week coulomb efficiency is charging capacity / discharging capacity×100%.

[0061] from Figure 7 The comparison results of the first control group show that compared with the 2016 button battery E-FeCoNiAlZn@CNT (73.4%), the 2016 button battery A-FeCoNiAlZn@CNT-Li 22 Sn5@EVA (20%Li 22 The first efficiency of the negative electrode of Sn5@EVA) was increased to 98.1%.

[0062] from Figure 8 The comparison results of the second control group show that compared with the 2016 button battery F-Cu2NiAlZn@CNT (75.6%), the 2016 button battery B-Cu2NiAlZn@CNT-Li 22 Sn5@PVDF-HFP(20%Li 22 The first efficiency of the negative electrode of Sn5@PVDF-HFP) was increased to 98.5%.

[0063] from Fig. 9 The comparison results of the third control group show that compared with the 2016 button battery G-FeCoNiAlZn@CNT (73.4%), the 2016 button battery C-FeCoNiAlZn@CNT-Li 22 Sn5@PP (10%Li 22 The first efficiency of the negative electrode of Sn5@PP) was increased to 99.1%.

[0064] from Fig.10 The comparison results of the fourth control group show that compared with the 2016 button battery H-FeCoNiAlZn@CNT (73.4%), the 2016 button battery D-FeCoNiAlZn@CNT-Li 22 Sn5@PAN (20%Li 22 The first efficiency of the negative electrode of Sn5@PAN) was increased to 98.2%.

[0065] 2) FeCoNiAlZn@CNT-Li obtained in Example 1 22 Sn5@EVA electrode and FeCoNiAlZn@CNT electrode obtained in comparative example 1 showed good stability at 1 mA·cm -2 , 3 mAh·cm- 2 The coulombic efficiency of the following cycle is shown in Figure 2. Fig.11 As shown, it can be seen that FeCoNiAlZn@CNT-Li22 The average coulombic efficiency of the Sn5@EVA half-cell in the first 200 cycles is as high as 98.6%, almost close to 100%. Although the coulombic efficiency of the FeCoNiAlZn@CNT half-cell is relatively stable in the first 100 cycles at the same current density and deposition amount, it then shows drastic curve fluctuations. At the same time, the coulombic efficiency value is even lower than 65.8% after 100 cycles.

[0066] 3) FeCoNiAlZn@CNT-Li obtained in Example 1 22 The Sn5@EVA electrode and the FeCoNiAlZn@CNT electrode obtained in Comparative Example 1 were matched with the NCM811 positive electrode to assemble a full battery. Fig.12 As shown in the figure, the capacity retention rate of the full battery matched with FeCoNiAlZn@CNT electrode and NCM811 positive electrode after 100 cycles at 0.5C rate is only 74.5%, while the capacity retention rate of FeCoNiAlZn@CNT-Li 22 The full battery assembled with Sn5@EVA negative electrode and NCM811 positive electrode has a retention rate of 90.1% after 100 cycles at the same rate, showing excellent cycle stability.

[0067] Therefore, the present invention adopts the above-mentioned method for preparing a lithium metal negative electrode with an ultra-thin lithium-philic high-entropy alloy interface layer, by dispersing a high-entropy alloy, a lithium-tin alloy powder and a hydrophobic polymer in a non-organic solvent, and coating it on a copper foil, and obtaining a negative electrode with a pre-physical and chemical interface layer of a high-entropy alloy after drying; wherein the catalytic elements in the high-entropy alloy can induce carbon nanotubes to form a 3D conductive network skeleton, which can not only effectively reduce the current density of the electrode, but also accommodate lithium metal deposition, and at the same time activate the release of lithium ions in the lithium-tin alloy for pre-replenishment of lithium, thereby inhibiting the generation of lithium dendrites and "dead lithium", slowing down the volume change of the lithium metal negative electrode during the charge and discharge cycle, and improving the cycle stability of the battery.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer, characterized in that: The following steps are involved: S1. Preparing a high-entropy alloy composite material coated with carbon nanotubes: dissolving zinc nitrate, aluminum nitrate and other nitrates in deionized water and stirring to obtain a nitrate solution, adding citric acid to the nitrate solution to prepare a high-entropy alloy precursor, and grinding the high-entropy alloy precursor to obtain a high-entropy alloy precursor powder; preparing a high-entropy alloy composite material coated with carbon nanotubes by recrystallization of the high-entropy alloy precursor powder in an atmosphere of an inert gas and acetylene mixed gas; S2. Preparation of lithium-tin alloy particles: In an inert atmosphere, nano-tin particles with a particle size less than 200 nm and lithium metal are mixed in a molar ratio of 1-10:4.4-50, and heated at a temperature of 200°C-450°C for 6h-24h to obtain a lithium-tin alloy phase Li x Sn, grinding and sieving the lithium-tin alloy phase to obtain lithium-tin alloy particles; S3. In an inert atmosphere, a high entropy alloy composite material coated with carbon nanotubes and a hydrophobic polymer are dispersed in a non-polar solvent in a ratio of 6-12:1 to form a mixed solution. Lithium-tin alloy particles are added to the mixed solution and stirred evenly. A scraper is used to directly apply a certain thickness of the mixed solution on a copper foil. The mixed solution is then vacuum dried at a temperature of 60°C-120°C for 12h-24h to obtain a lithium metal negative electrode having a pre-lithiation interface layer of a high entropy alloy.

2. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S1, the molar ratio of zinc nitrate to aluminum nitrate is 1:1, and the molar ratio of zinc nitrate to other nitrates is 1:

1.

3. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S1, the other nitrates are one or more of nickel nitrate, iron nitrate and cobalt nitrate.

4. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S1, the molar ratio of citric acid to the total amount of nitrate solution is 1:

1. The preparation of the high entropy alloy precursor specifically includes the following steps: S1-1, citric acid is dissolved in nitrate solution and stirred evenly to obtain a sol S1-2, placing the sol in an oven and heating it at 60°C to 100°C for 12h to 48h to obtain a dry gel; S1-3. The dry gel is placed in an inert atmosphere at 250° C. to 350° C. and heated for 25 min to 60 min for self-combustion to obtain a high entropy alloy precursor.

5. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S1, the specific steps of preparing a carbon nanotube-coated high entropy alloy composite material from a high entropy alloy precursor powder are as follows: the high entropy alloy precursor powder is spread flat on a magnetic boat, placed in a tubular furnace, an inert gas is introduced, and heated to 600°C-800°C at a heating rate of 2°C / min-15°C / min, and then an inert gas and acetylene mixed gas is introduced for 0.5h-1h, and the mixture is cooled with the furnace to obtain a carbon nanotube-coated high entropy alloy composite material.

6. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S3, the hydrophobic polymer is one or more of polyvinylidene fluoride-hexafluoropropylene, ethylene-vinyl acetate copolymer, polyvinylidene fluoride, octadecyl phosphate, polypropylene and polyacrylonitrile.

7. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S3, the input mass ratio of lithium-tin alloy particles to the high-entropy alloy composite material wrapped by carbon nanotubes is 1-3:

10.

8. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S3, the non-polar solvent is one or more of toluene, tetrahydrofuran, cyclohexane, methyl formate and 1,3-dioxolane.

9. The method for preparing a lithium metal negative electrode having an ultra-thin lithium-philic high entropy alloy interface layer according to claim 1, characterized in that: In step S3, the mixed solution is coated on the copper foil to a thickness of 2 μm-20 μm, and the gas flow ratio of the inert gas to acetylene is 5-10:1.

Citation Information

Patent Citations

  • Metal lithium composite material as well as preparation method and application thereof

    CN117673286A

  • Preparation method of lithium metal negative electrode of pre-lithiation interface layer of multi-component alloy

    CN117913281A

  • Negative pole piece for lithium metal battery, electrode assembly, lithium metal battery and electronic equipment

    CN118302891A

Cited By

  • Distributed cobalt-free high-entropy energy storage electrode and preparation method and application thereof

    CN120184177A

  • A distributed cobalt-free high-entropy energy storage electrode and its preparation method and application

    CN120184177B

  • High-entropy alloy pole piece and preparation method and application thereof

    CN120878756A